A Descriptive Study about Students’ Symptoms and Knowledge of Computer Vision Syndrome - Irawaty, Enny; Rasyid, Meriana; Tirtasari, Silviana; Novendy, Novendy; Lontoh, Susy Olivia (Muhammadiyah Medical Journal, 2021)
Background: The COVID-19 pandemic has had many impacts on various aspects of life, one of which is education. The education system has changed from face-to-face to online learning methods. Online learning methods make students more likely to use digital media such as computers, laptops or mobile phones. The use of digital media that occurs continuously and without being balanced with sufficient knowledge can certainly have impacts on eye health. One form of eye health problems that often arise due to the use of digital media is computer vision syndrome (CVS). Purposes: Therefore, it is necessary to conduct a study to see the picture of students' knowledge about this disorder. Methods: The method used in this research is cross-sectional descriptive. Result: The mean age of the respondents was 19.91±1.648 years. A total of 82.7% of respondents complained of having more than 5 symptoms and as many as 98.5% had CVS. 90.6% of respondents complained about fatigue eyes, followed by 80.5% complained about eye strain symptoms and 80.5% complained about headaches, 42.9% of respondents have a lack of knowledge about CVS and only 15.4% of respondents have a good level of knowledge about CVS. Conclusion: It can be concluded that respondents’ lack of knowledge about CVS is the cause of the high prevalence of CVS in students, so they don’t know how to prevent this CVS. Therefore, it is necessary to take actions to increase students' knowledge about this disorder, so that it doesn’t cause negative impacts on eye health in the future.